Structural analysis of membrane-bound retrovirus capsid proteins. - Barklis, E (1997)
We have developed a system for analysis of histidine-tagged (His-tagged) retrovirus core (Gag) proteins, assembled in vitro on lipid monolayers consisting of egg phosphatidylcholine (PC) plus the novel lipid DHGN. DHGN was shown to chelate nickel by atomic absorption spectrometry, and DHGN-containing monolayers specifically bound gold conjugates of His-tagged proteins. Using PC + DHGN monolayers, we examined membrane-bound arrays of an N-terminal His-tagged Moloney murine leukemia virus (M-MuLV) capsid (CA) protein, His-MoCA, and in vivo studies suggest that in vitro-derived His-MoCA arrays reflect some of the Gag protein interactions which occur in assembling virus particles. The His-MoCA proteins formed extensive two-dimensional (2D) protein crystals, with reflections out to 9.5 A resolution. The image-analyzed 2D projection of His-MoCA arrays revealed a distinct cage-like network. The asymmetry of the individual building blocks of the network led to the formation of two types of hexamer rings, surrounding protein-free cage holes. These results predict that Gag hexamers constitute a retrovirus core substructure, and that cage hole sizes define an exclusion limit for entry of retrovirus envelope proteins, or other plasma membrane proteins, into virus particles. We believe that the 2D crystallization method will permit the detailed analysis of retroviral Gag proteins and other His-tagged proteins.